History of the Origin of Piano in the Science of Instrument Performance - Z. Ziyavutdinova (Researchparks Publishing, 2021)
in this article, the appearance of the keyboard (piano) has a long history. The first musical instrument to appear in ancient Rome was the monochord. This instrument was in the form of a one-string box, which was gradually improved with the addition of wires. The article explains how his keys were created, who invented them and named the instrument